Eyelid Margin Inflammation: Pathophysiology, Diagnosis and Management Approaches - Szcześniak, Grzegorz; Kiełczewska, Aleksandra; Kiełczewska, Anna (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Eyelid margin inflammation is a commonly reported syndrome of ophthalmic complaints. It is a chronic, multifactorial disorder of the eyelid margins that significantly impacts the visual function and quality of life of patients across all age groups. Establishing the epidemiology is challenging, and the diagnosis relies primarily on a physical examination combined with a thorough ophthalmological assessment, potentially supplemented by additional tests. The condition is recurrent, often necessitating long-term treatment. Successful management requires close collaboration between the specialist and the patient, which demands commitment and patience. Eyelid margin inflammation manifests through various symptoms, such as burning, itching, dryness, or a feeling of sand in the eyes. This condition is characterized by a wide range of symptoms with varying severity, contributing to the complexity of its diagnosis and treatment. This review examines the diagnostic approaches and treatment strategies for eyelid margin inflammation, focusing on the most common underlying factors. Materials and Methods: A comprehensive survey of articles published in scientific journals was conducted via the online research platforms PubMed and Google Scholar. Articles were searched by entering keywords in the appropriate configuration: “eyelid rim inflammation”, “ Meibomian gland dysfunction”, “demodex”. Description of current knowledge: Studies have indicated that the approach to diagnosing and managing eyelid margin inflammation is largely contingent on the underlying cause and the intensity of the patient's symptoms. Keywords: “eyelid rim inflammation”, “ Meibomian gland dysfunction”, “demodex”.